2008
DOI: 10.1007/s10531-008-9535-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of population density on forest structure and species richness and diversity of trees in Kampong Thom Province, Cambodia

Abstract: This study examined differences in stand structure, tree species richness, and tree species diversity in relation to population density in Kampong Thom Province, Cambodia. Tree data were obtained from a 1997 forest inventory involving 60 clusters (540 plots) systematically distributed over 30% of the provincial forest area. Spatially referenced population data were obtained from the 1998 national population census. The average number of trees per cluster was 356/ha, the average basal area, 23 m 2 /ha, the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…In total, 71 tree individuals representing 53 species of 27 families from DEF and 116 tree individuals representing 54 species of 22 families from DDF were collected (Appendixes 1 & 2). Most collected species were common tree species, which covered dominant canopy species, in DEF and DDF in Kampong Thom and Kratie Provinces (Tagane et al 2015, Top et al 2009, Toyama et al 2013. The nomenclature was checked in The Plant List, version 1.1 (http://www.theplantlist.org/).…”
Section: Wood Core Sampling and Plant Materialsmentioning
confidence: 99%
“…In total, 71 tree individuals representing 53 species of 27 families from DEF and 116 tree individuals representing 54 species of 22 families from DDF were collected (Appendixes 1 & 2). Most collected species were common tree species, which covered dominant canopy species, in DEF and DDF in Kampong Thom and Kratie Provinces (Tagane et al 2015, Top et al 2009, Toyama et al 2013. The nomenclature was checked in The Plant List, version 1.1 (http://www.theplantlist.org/).…”
Section: Wood Core Sampling and Plant Materialsmentioning
confidence: 99%
“…Without the basic understanding about the structure of a community, it is impossible to know its functioning. Thus a lot of phytosociological studies have been conducted throughout the world to understand the structure of different forest communities (Campbell et al, 1986;Timilsina et al, 2007;Top et al, 2009;Sambare et al, 2011;Erenso et al, 2014). In Indian scenario, several phytosociological studies have also been performed in different tropical forests: Western India (Sharma and Upadhyaya, 2002;Panchal and Pandey, 2004;Krishna et al, 2014), Peninsular India (Parthasarathy et al, 1992;Visalakshi, 1995;Parthasarathy, 1999;Mani and Parthasarathy, 2005;Gunaga et al, 2013), North East India (Bhuyan et al, 2003;Kumar et al, 2006;Kibria and Saha, 2011;Sarkar and Devi, 2014) and Northern India (Singh and Singh, 1991;Sagar et al, 2003;Pandey and Shukla, 2003;Chauhan et al, 2008;Tripathi and Singh, 2009;Behera et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The calculated value of evenness index that are almost similar for each category and index of dominance of the study areas revealed that the total number of individuals are more evenly distributed among all species present at the two study sites. Rahman et al [91], Rahman et al [92], and Top et al [93] believed that the higher the value of diversity, the greater the stability of community will be.…”
Section: Consensus On Managing Ailments Among Informantsmentioning
confidence: 99%